Tradução e adaptação transcultural do questionário Instructional Materials Motivation Survey (IMMS) para o português do Brasil - Garcia, Victor Cézar Sano (2020)
In the current scenario of medical education, several modalities of active methodologies, including educational games (gamification) have been used as learning tools in order to increase student motivation. In this context, assessing motivation can contribute to the analysis and decision of a more efficient teaching and learning proposal. To translate and cross-culturally adapt the Instructional Materials Motivation Survey - IMMS instrument, which is based on the ARCS model, which assesses motivation through the following areas: attention, relevance, trust and satisfaction. The original English IMMS version was initially translated into brazilian portuguese and subjected to a cross-cultural adaptation. This version was then translated into English. A pre-final version was applied to 30 individuals (students and teachers) of the medical school, in order to eliminate doubts regarding the understanding of the sentences. The final version of the adapted instrument was applied to 52 medical students to assess the internal consistency of the sentences. In the process of translation and cross-cultural adaptation did reach all equivalences: semantic, idiomatic, cultural and conceptual. In the evaluation of the internal consistency of the 52 students who underwent educational activity, 48 of them responded to the IMMS instrument, translated and adapted to Portuguese and were included in the analysis. The instrument had internal consistency of 0.718, evaluated through Cronbach's alpha. Evaluating the removal of each item, the alpha value ranged from 0.683 to 0.749. Students had an average motivation score of 3.66 (73.2% of motivation), ranging from 1.83 to 5.00. The final version of the IMMS instrument, after the process of translation and cross-cultural adaptation, maintained all 36 (Thirty six) sentences and also 3 (three) instructions of the original instrument and presented good internal consistency